THE GREEN MARKETING EVALUATION IN MIDDLE EAST - shukri, Sakinah mohd; Yajid, Mohd Shukri Ab; Tham, Jacquline (International Journal of Psychosocial Rehabilitation, 2020)
In this green marketing process, we came into contact with the small Aalborg‐based distribution company Laie Asl, which is looking to enter the Iranian market as Iranian distributors for a green product range of handcrafted Shoes and home décor from the Thai, but American‐based, wholesale distributor Pars Laminate. We found this an intriguing project. Firstly, because of the complexity of the roles of the parties involved seeing that Laie Asl has a contract to be the Iranian distributor for another manufacturer, wholesale distributor and brand, representing the question of Laie Asls own visibility, image and decision‐making rights in the marketing and sales process. Secondly, because it is interesting to see how this manufacturing and sales structure corresponds with the market demands for green authenticity as described above.